An investigation of how South African Small and Medium Enterprises use ICT and dynamic capabilities to achieve competitive advantage - Adeniran, Tejumade Victoria (Department of Information Systems, 2014)
This study sets out to investigate how South African Small and Medium Enterprises (SMEs) use Information and Communication Technology (ICT) and Dynamic Capabilities (DCs) to achieve competitive advantage in a changing business environment. The study explores the purposes for which South African SMEs use ICT in a changing environment, as well as the types of organisational capabilities or DCs that can significantly impact on competitive advantage within the SMEs. This study examines the contingent effect of firm size and age on the ICT capabilities, ICT utilisation, and absorptive and innovative capabilities of South African SMEs.